A Case of Visceral Leishmaniasis Characterized by Fever of Unknown Origin and Nodular Lesions in the Spleen - Yakup Gezer; Erol Handemir; Arzu Tarakçı; Muhammet Rıdvan Tayşi; A Basturk; Salih Cırık (Genel Tıp Dergisi)

(untitled)
Introduction: Leishmaniasis is a zoonosis caused by Leishmania spp. parasites through the bite of infected female sandflies and has three main forms: visceral (VL), cutaneous (CL) and mucocutaneous (MCL). VL is endemic in many countries around the world. It is on the World Health Organisation's (WHO) list of neglected diseases and is difficult to diagnose due to its non-specific clinical manifestations. VL is characterised by fever, hepatosplenomegaly and bone marrow suppression. The diagnosis is made by the presence of amastigotes in tissue or blood samples or serological and DNA-based techniques. Case: Our patient was a 30-year-old male did not have any immunodeficiency. He was characterised by persistent fever, pancytopenia, hepatosplenomegaly and multiple millimetric hypoechoic solid nodules in the spleen. The diagnosis of VL was confirmed using all three parasitological, serological and molecular methods. Cure was achieved by treatment with liposomal amphotericin B (L-AmB). Discussion: VL should be considered in the differential diagnosis of patients with fever of unknown cause, pancytopenia and hepatosplenomegaly. The presence of solid nodular lesions in the spleen may also shed light in favour of VL